Los glacis de la cuenca de Mianda de Ebro (Burgos): significado climático y evolución geomorfológica - Soria Jaúregui, Ángel; González Amuchástegui, María José (Geographicalia, 2014)
Glacis of the Miranda de Ebro basin, which constitute one of the most dominant features in the local landscape, are analysed in this study. Two different levels are described whose topographic, morphological and sedimentological characteristics identify them as glacis. The environmental significance of these formations and its correlation with alluvial terraces of the Ebro River has enabled the establishment of a chronology for both levels, relating their formation to isotopic stages 2 and 4, within a coherent regional setting.
Keywords: Glacis; Miranda de Ebro; geomorphological evolution; Quaternary